Building Stability Between Host and Refugee Communities : Evidence from a TVET Program in Jordan and Lebanon - Ferguson, Neil T. N.; Wolfe, Rebecca J.; Amine, Laila; Ramadi, Eric; Shahin, Lina (World Bank, Washington, DC, 2022)
The resettlement of refugees in host communities increases (perceived) competition for scarce economic and non-economic resources, which can contribute to tensions between the communities. This study tests the impact of a TVET program in Jordan and Lebanon that aims to tackle stresses associated with competition, particularly in the labor market. The authors test the impact of the program on economic outcomes, economic and life optimism, experience and perception of economic competition and ingroup-outgroup discrimination using a range of survey measures and behavioral experiments. They also conduct heterogeneity analyses to assess whether the intervention affects host and refugee communities similarly. The authors show that by the end of the training, the program has not yet achieved its employment aims for either hosts or refugees. However, for refugees, there are significant improvements in optimism and decreases in the experience of short-term economic stress. There are also improvements in inter-group behavior for refugees. These results provide insights on how to better tailor labor market programs to host and refugees while being conflict sensitive.